Dissolution of Microcrystalline Cellulose in Phosphoric Acid—Molecular Changes and Kinetics - Pingkai Ouyang; Zhenjiang Li; Shijie Liu; Jun Zhang; Tianming Chen; Lu Lin; Junhua Zhang; Jingqiang Zhang (Molecules, 2009)
In this study, we aimed to dissolve microcrystalline cellulose (MCC) with phosphoric acid to obtain high-quality fermentable saccharides. MCC was directly dissolved in phosphoric acid (the concentration was 83%) for 10 hours at temperatures of 30, 50, and 70 °C. The structural changes of MCC were determined in detail with X-ray powder diffraction, solid-state cross-polarization magic angle spinning 13C-NMR, and X-ray photoelectron spectroscopy. The kinetics of MCC decrystallization during treatment with phosphoric acid was also compared at 30, 50, and 70 °C. With the assumption of first order kinetics, the Arrhenius parameters of K, A0 and Ea were calculated. The rate constants of decrystallization reaction (K) were 0.06, 0.17, and 0.12 h-1 respectively. The pre-exponential factor (A0) was 1.2 × 106 h-1, and the activation energy (Ea) was 42.4 kJ/mol.